2021
DOI: 10.1016/j.eats.2021.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Bicortical Titanium Tenodesis Button With Double-Row Fixation for the Treatment of Proximal Rectus Femoris Avulsion: Review of Literature and Surgical Technique

Abstract: In adult populations, rectus femoris avulsions are reported in professional soccer and football players but are noted to be exceptionally rare. No gold standard or recommendations exist for this injury; however, in cases of avulsion at the anterior inferior iliac spine, positive outcomes appear to result from rest, immobilization, and rehabilitation. Surgery is typically reserved for cases with large retractions of bone fragments or unsuccessful nonoperative treatment. Surgical treatment methods vary from dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“… 4 , 7 , 15 , 18 , 21 , 23 For PRF injuries, suture anchor repair and tenodesis are 2 common repair techniques. 4 , 12 , 15 , 21 Clinical studies have reported satisfactory postoperative results for both techniques, 1 , 7 , 13 , 15 , 18 , 21 - 23 and there is no consensus on which technique is superior. 15 , 17 Furthermore, no biomechanical studies have evaluated the time-zero strength of these repair techniques for PRF injuries.…”
mentioning
confidence: 99%
“… 4 , 7 , 15 , 18 , 21 , 23 For PRF injuries, suture anchor repair and tenodesis are 2 common repair techniques. 4 , 12 , 15 , 21 Clinical studies have reported satisfactory postoperative results for both techniques, 1 , 7 , 13 , 15 , 18 , 21 - 23 and there is no consensus on which technique is superior. 15 , 17 Furthermore, no biomechanical studies have evaluated the time-zero strength of these repair techniques for PRF injuries.…”
mentioning
confidence: 99%